2017
DOI: 10.1039/c7ra04047d
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective synthesis of bamboo-structure carbon nanotubes from coal for reversible lithium storage

Abstract: Carbon nanotubes (CNTs) with special structures offers great benefits for energy storage applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Bamboostructure coal-derived carbon nanotubes were synthesized via an arc discharge method with the catalyst Ni−Sm 2 O 3 for reversible Li storage with a specific capacity of 450.1 mAh g −1 . 191 Gao et al 192 reported that coal-based carbon interconnected with highly crystallized Co 2 Mo 3 O 8 (CMO) hexagonal nanoplates was designed by using a molten-salt-assisted process. This material was used as an anode in a Li-ion battery having an impressive specific capacity of 1075 mAh g −1 at 200 mAg −1 due to the porous structure of carbon materials with abundant active sites for Li storage (Figure 8).…”
Section: Coal-derived Activated Carbon As Anode Materials In Li-ion B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bamboostructure coal-derived carbon nanotubes were synthesized via an arc discharge method with the catalyst Ni−Sm 2 O 3 for reversible Li storage with a specific capacity of 450.1 mAh g −1 . 191 Gao et al 192 reported that coal-based carbon interconnected with highly crystallized Co 2 Mo 3 O 8 (CMO) hexagonal nanoplates was designed by using a molten-salt-assisted process. This material was used as an anode in a Li-ion battery having an impressive specific capacity of 1075 mAh g −1 at 200 mAg −1 due to the porous structure of carbon materials with abundant active sites for Li storage (Figure 8).…”
Section: Coal-derived Activated Carbon As Anode Materials In Li-ion B...mentioning
confidence: 99%
“…This anode was surface modified by nitrogen functional groups through gaseous NO treatment, either with or without prior steam activation. Bamboo-structure coal-derived carbon nanotubes were synthesized via an arc discharge method with the catalyst Ni–Sm 2 O 3 for reversible Li storage with a specific capacity of 450.1 mAh g –1 . Gao et al reported that coal-based carbon interconnected with highly crystallized Co 2 Mo 3 O 8 (CMO) hexagonal nanoplates was designed by using a molten-salt-assisted process.…”
Section: Coal-derived Activated Carbon As Anode Materials In Li-ion B...mentioning
confidence: 99%
“…Moreover, two strong bands are observed for the FRC at 1340 and 1585 cm –1 , assigning to the disordered (D) band and the graphite (G) band. The I D / I G ratio of FRC is 0.81, which is higher than that of common carbon, indicating that FRC contains more defects and vacancies because of its puffed and loose structure, which will promote Li + and electron transport. , The increasing I D / I G ratios of the FRC/NP-Si@C composites (Figure d) with increasing Si loading verify that the introduction of Si can add the disorder degree of the compounds. The robust microsphere structure with 3D conducting nanosized porous channels can both enhance the conductivity and relieve the volume expansion of Si during an electrochemical reaction.…”
Section: Resultsmentioning
confidence: 90%
“…7). Carbon nanotube is a promising electrode for LIBs and was extracted from bituminous coal by Li et al (2017a). The nanotube got a special bamboo-like structure promoting reversible lithium storage via enlarged electrode-electrolyte interface and reduced diffusion distance of Li ions.…”
Section: Anode Materials In Batteriesmentioning
confidence: 99%